Pemanfaatan Instagram Sebagai Media Promosi Di PT. Mitra Sejati Rezeki - Evi Enitari Napitupulu; Rachel Mia L. Lbn. Toruan; Mega Ulva Sari Sihombing; Elwin Famaugu; Mar Sebastian Bidaya (Universitas Sari Mutiara Indonesia, 2024)
The more the internet develops, the faster and easier the flow of information exchange, this can make people more likely to communicate via the internet, one of which is Instagram social media. Instagram has features that are useful for marketing promotions, has a business account, and has weaknesses such as limited context, decreasing upload quality. The purpose of this study is to find out how the use of Instagram social media as a promotional media used by PT. Mitra Sejati Rezeki. This research method uses a descriptive approach with a qualitative research type and uses data collection with Observation, Interviews, and Documentation. The results of the study show that the use of Instagram social media as a promotional media for PT. Mitra Sejati Rezeki has had a good impact on the promotional activities carried out by the company, besides that PT. Mitra Sejati Rezeki has also utilized the Instagram social network as a promotional media because the Instagram social network has helped in promotional activities with the target market they want, because Instagram is considered more interactive and informative.